A miniaturized patch antenna with enhanced bandwidth by using reactive impedance surface ground and coplanar parasitic patches. Issue 7 (12th March 2020) - Meng, Fanji; Liu, Ying; Sharma, Satish K.
Abstract: In this article, a miniaturized hybrid patch antenna is proposed that shows improved matching bandwidth and almost invariant radiation patterns. This antenna consists of a driven patch, reactive impedance surface (RIS) based ground plane in addition to the coplanar parasitic patches. The simulated and measured results show that the proposed antenna offers fractional bandwidth of 28% (S11 = −10 dB, from 2.38 GHz to 3.18 GHz). When this antenna operates at 2.38 GHz, 2.68 GHz, 2.98 GHz, and 3.18 GHz, shows realized gain of 6.46 dBi, 6.69 dBi, 7.84 dBi, and 7.59 dBi, whereas the front‐to back (F/B) ratio is 15.62 dB, 20.15 dB, 20.67 dB and 20.92 dB, respectively. The pattern quality is very consistent over the matching bandwidth. Compared to the conventional patch antenna, dimension of the hybrid patch antenna has decreased by about 36%.